Trust, affect, and choice in parents' vaccination decision‐making and health‐care provider selection in Switzerland. Issue 1 (8th November 2021) - Deml, Michael J.; Buhl, Andrea; Huber, Benedikt M.; Burton‐Jeangros, Claudine; Tarr, Philip E.
Abstract: This article examines the relationships between biomedicine, complementary and alternative medicine (CAM) and parents' vaccination decision‐making in Switzerland. Our empirical evidence sheds light on an understudied phenomenon—parents switching from one doctor to another provider (often one offering CAM services) around issues that arise during vaccination consultations. This is important to understand since CAM is used by 25%–50% of the Swiss population and is integrated into the Swiss health‐care system when offered by biomedically trained medical doctors with additional CAM training. Qualitative data gathered from in‐depth semi‐structured interviews with parents ( N = 30) and ethnographic observations of vaccination consultations ( N = 16 biomedical consultations, N = 18 CAM consultations) demonstrate how there was not always a clear‐cut, direct relationship between (non)vaccination and parents' use of CAM and/or biomedicine. Borrowing from Hirschman ( Exit, voice, and loyalty: Responses to decline in firms, organizations, and states, Harvard Univ. Press, 1970), we frame our analysis by using the concepts of exit, voice and loyalty to describe parents' provider selection and vaccination decision‐making process, although only four families in the sample described switching solely because of vaccination‐related issues. Findings add to vaccine decision‐making literature by describing and analysing the underdiscussed provider‐switching phenomenon and by demonstrating the importance of parents' experiences of trust, affect and choice in vaccination consultations as they pursue the best health outcomes for their children.